A communication-assisted protection scheme for direct-current distribution networks. (15th August 2016) - Monadi, Mehdi; Zamani, M. Amin; Koch-Ciobotaru, Cosmin; Candela, Jose Ignacio; Rodriguez, Pedro
Abstract: One of the major issues associated with the implementation of direct-current distribution systems is the design of a proper protection scheme. The fault current characteristics in direct-current distribution systems are quite different than those in conventional alternating-current grids. Thus, the performance of conventional protection schemes can adversely be affected, and it is necessary to modify the conventional protection schemes or design new protection methods for direct-current networks. This paper proposes a multi-zone differential protection scheme for direct-current distribution systems embedding distributed generators. The proposed method provides a selective and fast protection through the use of a communication link between two sides of a protected feeder. Moreover, the method provides a differential-based backup for the adjacent relays, which can enhance the protection system reliability. In addition, the method proposed in this paper also utilizes directional over-current elements to provide backup protection if the communication network fails. The effectiveness of the proposed protection scheme is evaluated through comprehensive hardware-in-the-loop simulation studies to obtain more realistic results and to investigate the impact of the communication delay. The results show that the proposed method can provide a selective and fast protection and effectively protect components of direct-current distribution systems against different types of faults. Highlights: A multi-zone differential protection scheme is proposed for direct-current networks. The method provides differential backup to improve reliability of protection system. An additional directional overcurrent backup is used when communication is failed. Network mode, fault level and distributed generators' status do not impact the relay. To provide more realistic relay evaluation, hardware in the loop testing was used.